2022
DOI: 10.14516/fde.994
|View full text |Cite
|
Sign up to set email alerts
|

Precarización de la Educación para Jóvenes y Adultos. La configuración de políticas educativas en el contexto neoliberal chileno

Abstract: Las leyes y normas legislativas definen el marco de acción de las políticas educativas. En Chile, esto se traduce frecuentemente en una visión de mercado orientada por los principios de la nueva gestión pública. Ante este marco, la Educación Para Jóvenes y Adultos (EPJA) resulta un caso particular, condicionado por la rendición de cuentas y ajena de apoyos para brindar una respuesta educativa acorde a su idiosincrasia. Ante esto, emerge como objetivo de este trabajo describir las acciones que los diferentes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Its precursors are absenteeism, low performance, failure, grade repetition, and educational backwardness ( Jurado and Tejada, 2019 ). Hence, school dropout is a major cause of inequality and social exclusion and one of the most entrenched phenomena in education systems, affecting millions of vulnerable young and adult people ( Lee-St et al, 2018 ; Tarabini, 2020 ; Contreras-Villalobos et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its precursors are absenteeism, low performance, failure, grade repetition, and educational backwardness ( Jurado and Tejada, 2019 ). Hence, school dropout is a major cause of inequality and social exclusion and one of the most entrenched phenomena in education systems, affecting millions of vulnerable young and adult people ( Lee-St et al, 2018 ; Tarabini, 2020 ; Contreras-Villalobos et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the school level, research on school dropout has shown that school management is key in tackling this problem ( Mduma et al, 2019 ; Contreras-Villalobos et al, 2022 ). Certain factors at the institutional level can help keep students in school, including policies and legal regulations, resources ( Alvariño et al, 2000 ), and school governance that determine how schools are organized and managed ( Ball, 2000 ).…”
Section: Introductionmentioning
confidence: 99%